OPTIMALISASI KINERJA ALAT GALI MUAT DAN ALAT ANGKUT UNTUK MENCAPAI TARGET PRODUKSI OVERBURDEN MENGGUNAKAN METODE QUALITY CONTROL CIRCLE DI PIT 1 TIMUR PADA TAMBANG TERBUKA PT. ALLIED INDO COAL JAYA, PARAMBAHAN, SAWAHLUNTO, SUMATERA BARAT - Aldi Fajri; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2021)
PT. Allied Indo Coal Jaya is a company engaged in coal mining business. Mining methods applied by PT. Allied Indo Coal Jaya is an open pit mining and underground mine method. In the stripping and transportation activities of overburden in pit 1 east of PT. Allied Indo Coal Jaya operates 2 cat 330D2 L backhoe excavators as a load digging tool and 8 units of HINO 500 FM 260 JD dump truck transport equipment. The problem that often occurs in overburden removal activities is the amount of time obstacles that can be avoided by loading and conveyance. This causes the performance of loading and carrying equipment is not optimal so that the actual productivity achievement in October 2020 is only 61,870.72 bcm / month while the company's target is 110,000 bcm / month.A production management study was conducted by applying the Quality Control Cycle (QCC) method. This method makes it possible to conduct a review of the optimization of the performance of loading-carry digging tools and the obstacles experienced during the production process. The study began by recalculating the initial conditions taking into account the mining equipment used, namely CAT 330D2 L excavators and DT HINO 500 FM 260 JD. The actual productivity of 2 units of CAT 330D2 L excavators reached 62,381.28 bcm/ month and DT HINO FM 260 JD reached 58,027.58 bcm / month with a total of 8 units of DT, the match factor of heavy equipment reached 0.97.After evaluating the Fishbone Diagram, it is known that there are major problems, namely environmental factors, equipment, materials and man power that affect working time. The results showed that productivity increased with equipment of 2 units of CAT 330D2 L excavators by 110,461.46 bcm / month and production of 8 units of DT increased by 106,962,578 bcm. These results show that the performance of the tool can be improved to achieve the planned monthly targets. Keywords. Productivity, Exca CAT 330, DT HINO 500, QCC Methods